Penentuan status mutu air sungai di kegiatan konstruksi PLTU Kotabaru dengan STORET dan Indeks Pencemaran - Lanang, Ragil Naga; Sururi, Moh. Rangga (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2022)
PLTU Kotabaru (2 x 7 MW) is a power plant that has 2 turbines with a capacity of 7 MW each and is located in Sigam Village, Kota Baru Regency, South Kalimantan Province. Surface water monitoring was carried out to see the impact caused by the construction of the Kotabaru PLTU in affecting the quality of surface water by determining its quality status. Parameters that exceed the quality standard are TSS, TDS, BOD, COD, DO, total coliform and fecal coliform. The STORET method identified that the classification of surface water quality was classified as heavily polluted. While the pollution index method identified that the classification of surface water quality was included in the lightly polluted category. The high quality standards in several parameters were not caused by the construction activities of the PLTU Kotabaru (2 x 7 MW) but from domestic activities in the form of sewage disposal and industrial activities around the Kemuning River.